Elipsis Posposisi Bahasa Jepang dalam Komik Akira Karya Hiromasa Okushima - Mhd. Pujiono; Abdul Gapur; Taulia Taulia (Ranah: Jurnal Kajian Bahasa, 2023)
In the context of everyday conversation, there is a phenomenon of ellipsis or disappearance in Japanese. One element of the word class that experiences ellipsis is postposition, which is a word class that plays an essential role in clarifying the function of a word in a sentence. This study examines the postpositional ellipsis in the Japanese conversation's comic Akira No. 2 by Hiromasa Okushima. The aim is to explain the form and process of the occurrence of Japanese postpositional ellipsis in conversation. This study uses a qualitative approach with a descriptive method. The data are conversational sentences with a postpositional ellipsis originating from the comic Akira No. 2 by Hiromasa Okushima Volume 1, chapter 1. Reading and note-taking techniques are used in data collection. The results indicate that there are postposition ellipsis wa (は), ga (が), no (の), e (へ), ni (に), o (を), and ka (か) occur in conversations between characters. The process of postposition ellipsis is influenced by the context of the conversation and occurs in character dialogue in comics in informal situations. Proposition ellipsis does not change the information or message in the sentence so that the interlocutor still understands the speaker's intent.